Beyond the Domestic Sphere: Reframing Muslim Husband-Wife Relations through Mubādalah in Indonesian Social Media - Nur Lailatul Musyafaah; Hammis Syafaq; Mohammad Hadi Sucipto; Andina Najma Shavia (Zamzami Scholar Publishing, 2026)
The rapid expansion of social media has transformed Islamic norm production by shifting representations of Muslim family life from private domestic settings to digitally mediated public arenas. While existing studies on Muslim influencers largely emphasize piety performance and religious commodification, little attention has been paid to how Islamic marital ethics are renegotiated through everyday online representations. This qualitative netnographic study analyzes the Instagram accounts of Indonesian Muslim influencers Alfysaga and Fatmasarizar through the lens of mubādalah (reciprocity) to examine how gender roles are visually and narratively constructed. The findings reveal a participatory marital model grounded in shared domestic responsibilities, collaborative parenting, recognition of personal autonomy, and the affirmation of women’s emotional agency, subtly challenging hierarchical readings of qiwāmah. The article argues that Instagram operates as a site of digital sharia negotiation, where Islamic family norms are interactively interpreted and recalibrated. By integrating digital ethnography with Islamic legal-ethical analysis, this study contributed to Digital Sharia scholarship by demonstrating how mediated visibility reshapes contemporary Muslim marital authority.